Just-in-Time system in terms of real options - Rózsa, Andrea (Competitio, 2004)
The value creation process in a company and the competitive position are critically influenced by corporate resource allocation and proper valuation of investment alternatives. After the Second World War, capital budgeting and strategic planning emerged as two complementary but different systems for resource allocation. The real options approach developed in the ’80s may provide a useful tool for making a connection between capital budgeting and strategic management. Real options are implicit managerial and operating flexibilities embedded in many non-financial assets and liabilities. In a wider sense: “A real option is the investment in physical assets, human competence, and organisational capabilities that provide the opportunity to respond to future contingent events” (Kogut-Kulatilaka, 2001). This paper shows that Just-in-Time (JIT) system as management philosophy can be regarded as a knowledge-based or capability-based implicit strategy rather than a simple, easy-toimitate best practice approach. Moreover, implementation of JIT can be considered as a strategic investment. The presentation focuses on how the relation among strategic investments, developed technological systems and corporate strategy can be expressed through the real options view.